The Dispersion of Employees? Wage Increases and Firm Performance - Christian Grund; Niels Christian Westergård-Nielsen (Institute for the Study of Labor (IZA), 2004)
In this contribution we examine the interrelation between intra-firm wage increases and firm performance. Previous studies have focused on the dispersion of wages in order to examine for the empirical dominance of positive monetary incentives effects compared to adverse effects due to fairness considerations. We argue that the dispersion of wage increases rather than wage levels is a crucial measure for monetary incentives in firms. The larger the dispersion of wage increases the higher the amount of monetary incentives in firms. In contrast, huge wage inequality without any promotion possibilities does not induce any monetary incentives. Evidence from unique Danish linked employer employee data shows that large dispersion of wage growth within firms is generally connected with low firm performance. The results are mainly driven by white collar rather than blue collar workers.
Keywords: J31; M52; L25; 330; fairness; firm performance; inequality; monetary incentives; wage dispersion; wage increases; Lohnstruktur; Leistungsorientierte Vergütung; Vergütungssystem; Gerechtigkeit; Leistungsanreiz; Unternehmensentwicklung; Schätzung; Dänemark